Indecent proposal ; Vital linkage ; Beep-bopping with the band [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1993)
Senator Ernesto Maceda exposes the activites of young Filipina showbiz personalities who have been going to Brunei and getting paid good money to entertain. Dr. Armando Gustilo, a Filipino orthopedic surgeon revolutionized the science of artificial limbs and joints. First Lady Ming Ramos displaying her talent in music by joining the Executive Band.
Contents : Indecent proposal (17 min.) -- Vital linkage (15 min.) -- Beep-bopping with the band (13 min.).
Reporter, Luchie Cruz-Valdes.
VHS
Keywords: Prostitution -- Philippines; Arthritis -- Surgery -- Philippines; Women executives -- Philippines